Project Management in Prototyping an Online Table Reservation System - Antonius Felix; Vincentius Leornardo; Melcelyn Melcelyn; Deah Ananda (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
The rapid digital transformation in the food and beverage (F&B) industry has intensified demand for systematic and technology-driven approaches to restaurant operations, particularly in table reservation management. However, most restaurants continue to rely on manual reservation processes prone to miscommunication, double bookings, and operational inefficiency, while existing literature predominantly examines system development and project management in isolation. This study aims to design and implement a web-based online table reservation system for the F&B industry by integrating the Project Management Body of Knowledge (PMBOK) framework with the Systems Development Life Cycle (SDLC), thereby addressing the identified gap in the literature. A descriptive qualitative approach with a system development research design was employed; data were collected through observation, literature review, focus group discussions, and market analysis. The resulting system prototype incorporates features including online booking, QR-based check-in, secure digital payment, and real-time reservation management. Evaluation through scenario-based testing and User Acceptance Testing (UAT) indicates that the system reduces reservation errors, shortens waiting times, and improves user satisfaction compared to manual methods. Theoretically, this research contributes by demonstrating how PMBOK knowledge areas—including Scope, Time, Cost, Quality, and Risk Management—can be systematically mapped onto stages of digital system development. Practically, the study provides a replicable project management reference model for F&B businesses seeking to improve service quality and operational performance through structured digital transformation.